Addition and Omission in Translating Literary Works Case Study: Volume II Entitled ″Cosette″ of Victor Hugo′s ″Les Misérables″ Translated by Isabella F.Hapgood - BOUGHERARA, Chaabane; BENAICHA, Djalaleddine (Faculty of Letters and Foreign Languages Department of English, 2019)
The present research is about ′′ Addition and Omission in Literary Translation of the Volume II Entitled "Cosette" of Victor Hugo’s “Les Misérables” which translated into English by the English-Scottish translator Isabella Florence Hapgood. It aims first, to answer the reason for choosing addition and/or omission in translation studies. Second, confirming the possibility to convey what the author intended to communicate. Also, determining any given changes that occur in the meaning of the message when additions or/and omissions are applied in translation. In addition, to prove the hypothesis that metaphorical languages always have equivalents in any foreign given translated language . The descriptive and analytical methods are chosen to answer the preceding mentioned research questions. This study is made up of two theoretical chapters and practical one. The first two chapters are all about the review of literary translation and aim to identify the impact if using addition and omission by the translator while translating literary works .In addition, the difficulties that may face translators and criteria that maintain them meaningful and faithful translators. At last, in the practical chapter, we tried to project these concepts on the novel translated